Pengaruh Probabilitas Kebangkrutan, Profitabilitas, Keahlian Komite Audit, Dan Keaktifan Komite Audit Terhadap Audit Report Lag - Ayu Dewi Shinta; Made Dudy Satyawan (Universitas Negeri Surabaya, 2021)
The research aims to examine the effects of bankruptcy probability, profitability, audit committee expertice, and audit committee activity on audit report lag. The population used is mining company listed in IDX period of 2013-2018 with purposive sampling as sampling techniques and multiple regression as analysis techniques. The test result from SPSS version 23 have shown that bankruptcy probability, profitability, and audit committee activity can be effect on audit report lag, while audit committee expertice can be no effect on audit report lag.